Corporate Sustainability Reporting: Regulations of the International Sustainability Standards Board and the European Union - Kamiński, Ryszard (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2024)
The disclosure of enterprises’ achievements in the field of sustainable development requires the use of a specific set of indicators framed in a coherent reporting system. The aim of this article is to present and assess two international regulations that create systems for reporting social, environmental, including climate and management issues by enterprises. These are the standards developed by the International Sustainability Standards Board and legal regulations, including reporting standards adopted in the European Union. The discussion in the article shows that although both systems differ in their degree of maturity, they meet the basic challenges related to the need to inform about the goals and achievements of enterprises in the field of their sustainable development. Therefore, there is a chance for these systems to converge in the future.